2022
DOI: 10.1021/acs.orglett.2c02426
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light-Promoted Diazoacetates and Nitriles Generating Nitrilium Ions Trapped by Benzotriazoles and Carboxylic Acids

Abstract: A visible light-promoted generation of nitrilium ions from diazoacetates and nitriles has been developed. The reaction utilized visible light transformation of diazoacetates to the free carbene that could be trapped by nitriles to generate nitrilium ions, followed by nucleophilic attack on the benzotriazoles and carboxylic acids. This protocol provides an efficient and practical approach to N-imidoylbenzotriazoles and diacylglycine esters in good to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…More recently, in 2022, Zhao, Li and co-authors (Scheme 12a), 31 and Xuan and co-authors (Scheme 12b) 32 have simultaneously and independently reported a remarkable blue light-mediated cascade reaction employing alkyl diazoacetates 35 in the presence of carboxylic acids 47 and nitriles 48 to afford the corresponding non-symmetrical imides 49 via a Mumm rearrangement (Scheme 12c).…”
Section: Acceptor-only Diazo Compoundsmentioning
confidence: 99%
“…More recently, in 2022, Zhao, Li and co-authors (Scheme 12a), 31 and Xuan and co-authors (Scheme 12b) 32 have simultaneously and independently reported a remarkable blue light-mediated cascade reaction employing alkyl diazoacetates 35 in the presence of carboxylic acids 47 and nitriles 48 to afford the corresponding non-symmetrical imides 49 via a Mumm rearrangement (Scheme 12c).…”
Section: Acceptor-only Diazo Compoundsmentioning
confidence: 99%
“…g . aryldiazoacetates), [17a–h] aryl/aryl diazoalkanes, [17i–j] acceptor‐only diazoalkanes, [17k–l] as well as other types of diazo compounds (pyridotriazoles and cyclic diazoalkanes) were all suitable substrates to give carbene intermediates under sole visible light irradiation (Scheme 2). [17m–n] Among the photochemical cyclopropanation reactions reported, the aryldiazoacetates were the mostly investigated carbene precursors.…”
Section: Cyclopropanation By Photochemical Carbene Transformation Rea...mentioning
confidence: 99%
“…A plausible reaction mechanism based on above experimental results and literature reports is proposed in Scheme c. ,, First, under visible-light irradiation, ethyl diazoacetate 1 released a molecule of N 2 to give a carbene intermediate, which was trapped by acetonitrile to give the nitrile ylide. Protonation of the nitrile ylide provided the nitrilium ion intermediate.…”
mentioning
confidence: 90%
“…To our delight, the anticipated nitrile ylide formation/trapping reaction successfully occurred when benzoic acid 7 was involved. We found that the nitrile ylide intermediate could be trapped by benzoic acid to give intermediate A , which underwent a fast Mumm rearrangement to give imide 8 in an 87% yield. , Note that imides are important synthetic building blocks in organic synthesis and also have significant application value in the field of medicinal chemistry …”
mentioning
confidence: 93%